2015
DOI: 10.1093/schbul/sbv140
|View full text |Cite
|
Sign up to set email alerts
|

The Core Brain Region for Face Processing in Schizophrenia Lacks Face Selectivity

Abstract: These results show a lack of face-specific processing in the schizophrenic brain region presumably subserving face perception. This finding suggests boosting visual salience of face images as a potential therapeutic venue for improving face perception in this psychiatric disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…In this study, we did not observe significant differences in resting-state FC and clinical characteristics between the TCS and MTCS patients. Consistent with previous studies, [54][55][56] TCS and MTCS patients showed decreased FC patterns compared with HCs in our study, which also supports the disconnection hypothesis of schizophrenia. 54,57 Furthermore, in all patients with chronic schizophrenia, signals of full-range and short-range FC in the right fusiform gyrus, right inferior temporal gyrus, and right inferior occipital gyrus were associated with the onset age and the duration of illness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we did not observe significant differences in resting-state FC and clinical characteristics between the TCS and MTCS patients. Consistent with previous studies, [54][55][56] TCS and MTCS patients showed decreased FC patterns compared with HCs in our study, which also supports the disconnection hypothesis of schizophrenia. 54,57 Furthermore, in all patients with chronic schizophrenia, signals of full-range and short-range FC in the right fusiform gyrus, right inferior temporal gyrus, and right inferior occipital gyrus were associated with the onset age and the duration of illness.…”
Section: Discussionsupporting
confidence: 93%
“…60 The fusiform gyrus plays a major role in processing facial signals, and an aberrant state of the fusiform gyrus is related to abnormal facial processing in schizophrenia. 55,61,62 The alterations in the inferior occipital gyrus may be involved in facial processing in schizophrenia. 63 The altered connectivity in these regions correlated with the onset age and the disease course in schizophrenia, suggesting that decreased full-and short-range FC of the overlapping regions may reflect an ongoing pathological process of chronic schizophrenia.…”
Section: Overlapping Regions Between the Tcs And Mtcs Patientsmentioning
confidence: 99%
“…The participants of this study also participated in an fMRI study in which BOLD response in fusiform face area (FFA) were acquired using identical task paradigms (Maher et al 2015). The fMRI acquisition and result are summarized in Supplement 3.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we compared N170 responses and fMRI responses in FFA to the same face and tree stimuli and in the same participants. The combined analysis with the fMRI data, available from a recent study (Maher et al 2015), gives a better understanding of the relationship between spatial and temporal markers of face-specific processing in schizophrenia. A lack of face-specific processing may accompany altered spatial localization and temporal dynamics of cortical response, or a disrupted relationship between the two domains.…”
Section: Introductionmentioning
confidence: 99%
“…One consistent cognitive dysfunction in people diagnosed with schizophrenia involves non-emotional face processing (for reviews see Darke et al, 2013; Onitsuka et al, 2013; Watson, 2013; Bortolon et al, 2015; McCleery et al, 2015) both at behavioral (Chen, 2011; Maher et al, 2015, 2016) and physiological levels (Herrmann et al, 2004; Onitsuka et al, 2006; Tsunoda et al, 2012; Maher et al, 2016). …”
Section: Introductionmentioning
confidence: 99%